ORAL DEPENDENCY: A POTENTIAL RISK FACTOR FOR GASTRIC LESIONS - Waqas Manzoor; Bukhtawar Naz; Ali Boricha; Shumaila Ismail; Muhammad Akbar; Humaira Zakir; Hina Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Objective: To evaluate the correlation of oral addictions with the risk to develop the gastric lesions. Place & Duration of the study: The study was conducted at Isra University, Karachi and Hyderabad campus. From March 2024 to July 2025. Methodology: A cross sectional analytical study was done on 200 numbers of patients, both gender were included with any age range. The non-probability convenient sampling technique was adopted to enroll the patients after conformation of gastric lesion on gastroscopy and on the basis of history of the oral addiction and symptoms relatable. Patients with previous history of treatment and surgical intervention, any trauma and on chemotherapy were excluded. The finding were documented on proforma and data analyzed through SPSS. The qualitative data was presented in the form of Frequency and percentage, while the correlation was evaluated by applied Chi-square test. The P value was set at P=<0.05. Results: The Mean age of male was 46.23±0.51 and female was 56.471.34. Out of 200 patients the male was 61% and female was 39%. About 30% males and 50% of females consumed pan with correlation of 0.001, niswar, gutka and tobacco showed significant correlation among both gender. The 60% erosive and 72% non-erosive with significant correlation 0.021 in both gender among gutka consumers, 28% erosive and 46% non-erosive with 0.054 in both gender of niswar users. 51% erosive and 41% non- erosive among tobacco, 30% erosive and 50% non-erosive found in pan users. While 0.021% in users. 58% of non-erosive mucosal inflammation, 42% mucosa with erosions, and 34% ulceration was found on gastroscopy. 64% of male presented with epigastric pain, 72% females with epigastric discomfort, 65% of females with nausea, 43% females with vomiting, 61% females with bloating and 42% with oral ulcers. The positive correlation was found in epigastric pain and discomfort, nausea, vomiting and bloating in both genders. Conclusion: As the study results evidence the significant correlations of both genders with higher consumption of different oral tobacco based products, mostly pan, gutka, betel nuts, and niswar users. Mostly the erosive lesions were 60% in gutka, and 51% tobacco were reported. Non-erosive lesions were 72% with gutka and 50% in pan consumers. Most of the lesions were non-erosive, and about 42% erosive which is quite alarming.